FROM PLANNING TO THE ADOPTION OF THE STATE BUDGET: A LITERATURE REVIEW ON THE PROCESSES AND PRINCIPLES OF PUBLIC FINANCE MANAGEMENT - Putri Tunggal Dewi; Alvira Rizky Azzakia; Raihan Syahaqi Panjaitan; Iskandar Muda; Andy Mulia (JIAR : Journal Of International Accounting Research, 2025)
Based on a literature review, this study examines the process from planning to the enactment of the State Budget (APBN) and the principles underlying public financial management. Public financial management involves planning, implementation, oversight, and accountability, supported by the role of the House of Representatives (DPR) and the authority of the Minister of Finance as the State Treasurer. This study aims to analyze the application of transparency and accountability in APBN management and identify existing challenges and potential improvements. The method used is library research, involving the analysis of relevant literature. The findings show that transparency and accountability are essential for ensuring efficient and responsible use of public funds. However, challenges such as limited information access and complex oversight mechanisms persist. Therefore, improvements in information disclosure, financial reporting quality, and oversight systems are necessary to enhance public financial management.